The world of Rodin, 1840-1917 - Hale, William Harlan 1910-1974; Rodin, Auguste 1840-1917.; Boltin, Lee; Kessel, Dmitri; Editors of Time-Life Books; Time-Life Books ([Netherlands] B.V. Time-Life International, 1969)
An account of the life, work and times of the great French sculptor, Auguste Rodin.
Disturber of the peace -- Voyages of discovery -- A rage to produce -- Into the inferno -- A trio of humiliations -- The world's foremost sculptor -- Gift to the future -- Chronology of artists.
Includes bibliographical references (page 187) and index.